Analysis of Tourism Development on Socio-Economic Changes in The Community on Rinca Island, East Nusa Tenggara - Rosni, R; Narimo, Sabar (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to analyze the impact of tourism development on socio-economic changes in the community on Rinca Island, East Nusa Tenggara. The research method and results used a qualitative descriptive design. Celebrity endorsement; testimonials; purchase intention. The subjects of this study were local fishermen, souvenir vendors, the head of the Tourism Police (Poldarwis), village staff, BPD chairman. The results of this study indicate that analyzing tourism development impacts socioeconomic changes on Rinca Island, East Nusa Tenggara. This demonstrates that tourism has brought about changes in the local economy, leading to greater stability, in addition to income from marine resources. The tourism sector has created employment opportunities for local residents, including services as tour guides, accommodations for homeowners, handicrafts for souvenirs, and the use of sea transportation for tourists. Before tourism, the community was primarily engaged in fishing, which was the primary source of income for the Rinca Island community. Other changes in the social life of the Rinca Island community include increasingly prominent lifestyle competition, and more open social activities, both in the form of interaction, direct communication, and social media.